Strategies to address participant misrepresentation for eligibility in Web‐based research. Issue 1 (16th January 2014) - Kramer, Jessica; Rubin, Amy; Coster, Wendy; Helmuth, Eric; Hermos, John; Rosenbloom, David; Moed, Rich; Dooley, Meghan; Kao, Ying‐Chia; Liljenquist, Kendra; Brief, Deborah; Enggasser, Justin; et al.
Abstract Emerging methodological research suggests that the World Wide Web ("Web") is an appropriate venue for survey data collection, and a promising area for delivering behavioral intervention. However, the use of the Web for research raises concerns regarding sample validity, particularly when the Web is used for recruitment and enrollment. The purpose of this paper is to describe the challenges experienced in two different Web‐based studies in which participant misrepresentation threatened sample validity: a survey study and an online intervention study. The lessons learned from these experiences generated three types of strategies researchers can use to reduce the likelihood of participant misrepresentation for eligibility in Web‐based research. Examples of procedural/design strategies, technical/software strategies and data analytic strategies are provided along with the methodological strengths and limitations of specific strategies. The discussion includes a series of considerations to guide researchers in the selection of strategies that may be most appropriate given the aims, resources and target population of their studies. Copyright © 2014 John Wiley & Sons, Ltd.